Patient-physician discordance in assessment of adherence to inhaled controller medication: a cross-sectional analysis of two cohorts - Ricardo M Fernandes; Luís Taborda-Barata; Joana Carvalho; Georgeta Oliveira; Diana Bordalo; Marta Alves; Carlos Alves; Cristina Jácome; Ana Margarida Pereira; Rute Almeida; Manuel Ferreira-Magalhaes; Mariana Couto; et al. (BMJ Open)
Objective We aimed to compare patient’s and physician’s ratings of inhaled medication adherence and to identify predictors of patient-physician discordance.Design Baseline data from two prospective multicentre observational studies.Setting 29 allergy, pulmonology and paediatric secondary care outpatient clinics in Portugal.Participants 395 patients (≥13 years old) with persistent asthma.Measures Data on demographics, patient-physician relationship, upper airway control, asthma control, asthma treatment, forced expiratory volume in one second (FEV1) and healthcare use were collected. Patients and physicians independently assessed adherence to inhaled controller medication during the previous week using a 100 mm Visual Analogue Scale (VAS). Discordance was defined as classification in distinct VAS categories (low 0–50; medium 51–80; high 81–100) or as an absolute difference in VAS scores ≥10 mm. Correlation between patients’ and physicians’ VAS scores/categories was explored. A multinomial logistic regression identified the predictors of physician overestimation and underestimation.Results High inhaler adherence was reported both by patients (median (percentile 25 to percentile 75) 85 (65–95) mm; 53% VAS>80) and by physicians (84 (68–95) mm; 53% VAS>80). Correlation between patient and physician VAS scores was moderate (rs=0.580; p<0.001). Discordance occurred in 56% of cases: in 28% physicians overestimated adherence and in 27% underestimated. Low adherence as assessed by the physician (OR=27.35 (9.85 to 75.95)), FEV1 ≥80% (OR=2.59 (1.08 to 6.20)) and a first appointment (OR=5.63 (1.24 to 25.56)) were predictors of underestimation. An uncontrolled asthma (OR=2.33 (1.25 to 4.34)), uncontrolled upper airway disease (OR=2.86 (1.35 to 6.04)) and prescription of short-acting beta-agonists alone (OR=3.05 (1.15 to 8.08)) were associated with overestimation. Medium adherence as assessed by the physician was significantly associated with higher risk of discordance, both for overestimation and underestimation of adherence (OR=14.50 (6.04 to 34.81); OR=2.21 (1.07 to 4.58)), while having a written action plan decreased the likelihood of discordance (OR=0.25 (0.12 to 0.52); OR=0.41 (0.22 to 0.78)) (R2=44%).Conclusion Although both patients and physicians report high inhaler adherence, discordance occurred in half of cases. Implementation of objective adherence measures and effective communication are needed to improve patient-physician agreement.